Geoquímica de las rocas del stock Chinchiná - Santa Rosa (2004)
In this study, appears the first analytical results of major elements, trace and rare earth of the protomilonitas of the Stock Chinchiná-Santa Rosa, it is in the Western flank of the Central belt, between the faults Silvia-Pijao, eastwards and Cauca-Almaguer, on the west. The geochemistry characterization in the rocks that they formed in the Stock indicates that this one belongs to the subalkaline series with character toleítico and they are clasified like gabbros and madaly as metagabbro that change according to the grade of deformation between the cataclasites and the milonites. Tectonic discrimination diagrams, allowed to establish that the generation of intrusive body in an dominion distensive of dorsal oceanic type N-MORB; the identification of this environment will allow to set this body in a geotectonic position, forming a part of a complex ophiolitic.